Electrode Arrangements for Continuous Measurement of Dispersion Conductivity in Lab Flotation Cells - Maldonado-Saavedra, M (Elsevier Ltd, 2017)
Electrical conductivity, an intensive property of materials, has been used in flotation for measuring important process variables such as froth depth, bias rate, solid and gas holdup. Most of these applications were based on a sensor that included a conductivity cell made up of metallic ring electrodes flush-mounted to the internal wall of a tube. The use of this approach in lab mechanical cells produces unreliable conductivity measurements as the introduction of the sensor in the relatively small volume of the unit significantly affects its hydrodynamics. A new approach was devised for measuring the conductivity of dispersions in the unit by using cell walls and impeller shaft as electrodes. The use of this approach led to the design of flotation cells that successfully measured the conductivity of sodium chloride solutions and slurries. Results demonstrated reproducible measurement of solution and slurry conductivities; calculations of solids holdup using Maxwell equation for slurries with pulp densities as high as 30% by weight showed relative holdup errors of about 2%. Testing of a cylindrical cell made with side-by-side cylinders of conducting stainless steel and non-conducting plastic, demonstrated that conductivity could be measured independently of the level in the cell, a result necessary for developing on-line measurement of gas holdup during lab flotation testing. © 2017 Elsevier Ltd